Association between time to adjuvant chemotherapy and survival in ovarian cancer patients treated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy - Sergei Iugai; Armando Sardi; Teresa Diaz-Montes; Mary Caitlin King; Vladislav Kovalik; Luis Felipe Falla-Zuniga; Kseniia Uzhegova; Panayotis Ledakis; Carol Nieroda; Vadim Gushchin (Gynecologic Oncology Reports)
Introduction: Delayed adjuvant chemotherapy (AC) worsens survival in advanced ovarian cancer (OC), but data on its impact after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS/HIPEC) is limited. We aimed to assess if delayed AC negatively affects survival in OC patients treated with CRS/HIPEC. Methods: We conducted a retrospective analysis of a single-center prospective database including FIGO stage III-IV epithelial OC patients who underwent initial CRS/HIPEC (upfront or interval) followed by AC. Patients were grouped into delayed AC (≥60 days) and no delay (<60 days). Patient characteristics were compared. Logistic regression identified risk factors for delay. Kaplan-Meier method and stratified Wilcoxon test were used for survival analysis. Results: Of 95 patients identified, 43 (45.3 %) were delayed, while 52 (54.7 %) had no delay. Delayed patients were significantly older (p = 0.013), had higher stage (p = 0.038) and peritoneal cancer index (PCI) (p = 0.020), more Clavien-Dindo grade III-IV complications (p = 0.002), and longer hospital stay (p = 0.003). Age ≥ 65 years (odds ratio [OR]: 5.25, p = 0.001), PCI ≥ 24 (OR: 3.89, p = 0.006), and stage IV (OR: 3.28, p = 0.017) were associated with a higher likelihood of delay. After adjusting for stage, comorbidities, complete cytoreduction (CC)-score, and CRS type, there were no significant differences in progression-free or overall (OS) survival between groups. Subgroup analysis found early chemotherapy worsened OS in CC-0 patients (p = 0.017), while CC-1 patients demonstrated a non-significant trend towards improved OS. Conclusion: Older OC patients with high tumor burden are more likely to have AC delay after CRS/HIPEC. Without clear survival benefits from early AC initiation, time to chemotherapy may be based on individual patient characteristics.